Tomograﬁa PCA aplicada a cubos de dados no infravermelho próximo para a galáxia Seyfert Mrk 1066 - Hennig, Moiré Gonçalves (2014)
In this work, we apply the PCA Tomography technique (Principal Component Analysis) to data cubes for the central region of the Seyfert 2 galaxy Mrk 1066. The observations were done with the NIFS (Near-infrared Integral Field Spectrograph) instrument at Gemini North Telescope in the spectral bands J and K and with spatial resolution of ∼35 pc. Mrk 1066 has been the subject of studies by our working group, with the application of traditional techniques (as ﬁtting of the emission-line proﬁles and measurements of stellar kinematics). Thus the use of the PCA Tomography in this work, which is a powerful statistical tool, is aimed to conﬁrm previous results obtained with the use of traditional techniques, and at the same time searching for details of the physics of the central region of this galaxy, not seen in traditional analysis. The PCA Tomography was applied to datacubes for J and K bands at distinct spectral and spatial regions in order to emphasize regions of interest. With the simultaneous analysis of the eigenvectors and tomograms, we highlight some results for the central region of Mrk 1066: 1) We detected a ring of molecular gas (H2) with a radius of ∼75 pc, not detected in previous works, which seems to be being fed by gas ﬂows along the spiral arms that originate in the ring; 2) we detected dust emission in an unresolved central structure, which was interpreted as being related to the presence of the dusty torus postulated by the uniﬁed model for AGNs (Active Galactic Nuclei); 3) emission of gas in a rotating disk in the plane of the galaxy was also detected, in agreement with previous studies; 4) we found outﬂows of ionized gas from the nucleus of Mrk 1066 associated with the radio jet, beyond phenomena with complex kinematics, not interpreted in this work. We construted ﬂux maps for the continuum emission and for the main emission lines present in the spectra of Mrk 1066 from reconstructed datacubes using only some eigenvectors in order to highlight physical phenomena. We observed a good correlation between the ﬂuxes of emission li- nes of the ionized gas and radio emission in some tomograms and investigated the origin of the [Fe II] line emission using line ratios. We found the following values [Fe II]λ1,2570µm/Paβ = 0,9 and [Fe II]λ1,2570µm/[P II]λ1,1886µm = 4,2. These values indicate that there may be a contribution by shocks due to radio jet to the [Fe II] excitation. The shocks release the Fe from grains of dust enhancing the Fe abundance and thus the ﬂuxes of the emission lines of the [Fe II] is increased.